Analysis of the Implementation of the Merdeka Curriculum Policy in Vocational High Schools: A Qualitative Research - Supriadi; Putra, Meiyaldi Eka (Indonesian Journal of Technical and Vocational Education Training, 2024)
The purpose of this research is to get an overview: 1). How is the implementation of the Merdeka Curriculum policy at vocational high school Pekanbaru city, 2) What are the obstacles to implementing the Merdeka Curriculum policy at vocational high school Pekanbaru city, and 3) What efforts have been taken to overcome various existing problems. Data collection techniques using active participation observation techniques, interviews and document studies. This study found that: 1) Implementation of the Merdeka Curriculum policy at vocational high school Pekanbaru city by implementing an education system in the realm of input, process and output; 2) Obstacles to the implementation of independent learning from vocational high school Pekanbaru city include (1) Fulfillment of industrial competence requires a programmed increase in teacher competency; (2) Changes in dynamic industry competency standards require sustainable curriculum development and fulfillment of adequate infrastructure; (3) Difficulties in facilitating learning effectively according to industrial culture; 3) Efforts to overcome existing obstacles from the implementation of independent learning are: a) Creating a cooperation agreement program between vocational high schools and Industry; (b) Develop learning methods that are able to create a working atmosphere like in a company; (c) Curriculum synchronization with partner industries for curriculum development; (d) Improving teacher competency in the context of meeting industry expectations.